STUDENTS’ PERCEPTION ON QUESTIONNING TECHNIQUE IN IMPROVING SPEAKING SKILL ABILITY AT ENGLISH EDUCATION STUDY PROGRAM - Milady Arini; Achmad Yudi Wahyudin (Faculty of Arts and Education, 2022)
This study aims to investigate students' perception toward the use of question techniques in improving students speaking skills at the tertiary level. Spoken skills and communication may play a very vital role to the students as their future profession might rely heavily on the use of the speaking ability. There are 24 participants in this study and it came from freshmen of English Education major. Based on the findings, it is clear that the students had a positive attitude toward the use of questioning techniques improving their speaking ability. The students perceived that they had an improvement, especially in fluency, accuracy, comprehension, vocabulary, and pronunciation. Moreover, the questioning technique led the students to be more active and participate in the learning activities. Besides, it triggered students to show their self-confidence. In short, it is implied that the more questioning technique is used, the better the students’ spoken ability might be.Keywords: Speaking Skill, question technique, perception, strategy, method